Influence of tryptophan on auxin-synthesizing ability of surfactant producer Acinetobacter calcoaceticus IMV B-7241 - Pirog, Tatiana; Leonova, Natalia; Piatetska, Daria; Klymenko, Natalia; Shevchuk, Tetiana (My University, 2020)
Introduction. The aim of this work is to determine the optimal tryptophan concentration and the time of its addition into the culture medium of the surfactant producer Acinetobacter calcoaceticus IMV B-7241 to achieve maximum auxin synthesis. Materials and methods. Cultivation was carried out on a liquid nutrient mineral medium using as a substrate of ethanol and waste of biodiesel production (crude glycerol). Tryptophan was added into the medium as a 1% solution in an amount of 100, 200 or 300 mg/L at the beginning of the process or at the end of the exponential growth phase (48 h of cultivation). Phytohormones were isolated by three times extraction with organic solvents from the supernatant of the culture liquid after extraction of surfactants. The qualitative and quantitative determination of gibberellins was carried out by high performance liquid chromatography. Results and discussion. The results show that regardless of the time of addition of tryptophan in the culture medium of the strain IMV B-7241 with crude glycerol a significant increase in the synthesis of auxins compared with those on the medium without this precursor was observed. The highest concentration of auxins was achieved by adding 300 mg/L of tryptophan into the medium with both substrates. Thus, A. calcoaceticus IMV B-7241 synthesized 1404.73, 1295.04 and 4850.98 μg/L of auxins on the crude glycerol medium with 100, 200 and 300 mg/L tryptophan added at the end of exponential phase respectively (and without precursor the concentration of auxins was 175,4 μg/L). Increased synthesis of auxins by strain IMV B-7241 correlated with the activity of tryptophan transaminase (key enzyme of biosynthesis): under cultivation on crude glycerol without precursor it was 163 nmol•min-1•mg-1 of protein, while in the presence of 300 mg/L of tryptophan added at the end of the exponential growth phase the activity was in 3.2 times higher – 526 nmol•min-1•mg-1 of protein. The highest concentration of auxins under cultivation on ethanol was achieved when 300 mg/L of tryptophan were added at the beginning of cultivation – 2261.66 μg/L. Conclusion. The result of the work established the possibility of increasing by one or two orders of magnitude of synthesized auxins in the case of addition into the culture medium of A. calcoaceticus IMV B-7241 low concentrations of the precursor of their biosynthesis.
Keywords: біосинтез; попередник; індоліл-оцтова кислота; поверхнево-активні речовини; Acinetobacter calcoaceticus ІМВ В-7241; кафедра біотехнології і мікробіології; biosynthesis; precursor; indolyl-acetic acid; surfactant